Multi-Faceted Bioactivity Assessment of an Exopolysaccharide from Limosilactobacillus fermentum NCDC400: Antioxidant, Antibacterial, and Immunomodulatory Proficiencies - Manorama Kumari; Basavaprabhu Haranahalli Nataraj; Writdhama G. Prasad; Syed Azmal Ali; Pradip V. Behare (Foods, 2023)
Exopolysaccharides (EPS) are acknowledged for their diverse functional and technological properties. This study presents the characterization of EPS400, an acidic exopolysaccharide sourced from the native probiotic Limosilactobacillus fermentum NCDC400. Notably, this strain has demonstrated previous capabilities in enhancing dairy food texture and displaying in vivo hypocholesterolemic activity. Our investigation aimed to unveil EPS400′s potential biological roles, encompassing antioxidant, antibacterial, and immunomodulatory activities. The results underscore EPS400′s prowess in scavenging radicals, including the 2,2-diphenyl-1-picrylhydrazyl radical, 2,2′-azino-di-(3-ethylbenzthiazoline sulfonic acid) radical, superoxide radical, hydroxyl radical, and chelating activity targeting the ferrous ion. Furthermore, EPS400 displayed substantial antibacterial effectiveness against prevalent food spoilage bacteria such as Pseudomonas aeruginosa NCDC105 and Micrococcus luteus. Remarkably, EPS400 exhibited the ability to modulate cytokine production, downregulating pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and nitric oxide, while concurrently promoting the release of anti-inflammatory cytokine IL-10 within lipopolysaccharide-activated murine primary macrophages. Additionally, EPS400 significantly (p ≤ 0.05) enhanced the phagocytic potential of macrophages. Collectively, our findings spotlight EPS400 as a promising contender endowed with significant antioxidant, antibacterial, and immunomodulatory attributes. These characteristics propose EPS400 as a potential pharmaceutical or bioactive component, with potential applications in the realm of functional food development.